2010
DOI: 10.1007/s12349-010-0036-5
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetry in obese women: comparison of two different operating indirect calorimeters together with the predictive equation of Harris and Benedict

Abstract: In patients with obesity, it is important to know the exact metabolic function in order to assess balanced nutritional support, reducing the risks of the initial situation. For an adequate detection of the resting metabolic rate (RMR), commonly indirect calorimeters are used. In the present study, two different indirect calorimeters [an expiratory collection open-circuit system (Fitmate) and a ventilated open-circuit system (Quark RMR)], were correlated and analysed for better adequacy. The predictive equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
0
2
0
4
Order By: Relevance
“…Studies analyzing the validity of BMR predictive equations for use in individuals with severe obesity found that the equations performed differently. For the same equation, there are studies showing overestimation, [17][18][19][20] underestimation, [21][22][23][24] and adequacy in the BMR estimate. 25,26 Although most BMR prediction equations take anthropometric variables into account, they are frequently generated based on a weight range that does not include severe obesity, which may be the origin of their bias.…”
Section: Introductionmentioning
confidence: 99%
“…Studies analyzing the validity of BMR predictive equations for use in individuals with severe obesity found that the equations performed differently. For the same equation, there are studies showing overestimation, [17][18][19][20] underestimation, [21][22][23][24] and adequacy in the BMR estimate. 25,26 Although most BMR prediction equations take anthropometric variables into account, they are frequently generated based on a weight range that does not include severe obesity, which may be the origin of their bias.…”
Section: Introductionmentioning
confidence: 99%
“…La calorimetría indirecta es una técnica sencilla, inocua, rápida y relativamente económica que, en la práctica clínica, se considera como método de referencia (9) . La mayoría de los modelos de estimación del GER se desarrolla utilizando la CI como criterio de validación, si bien es cierto que la precisión de esta técnica puede verse afectada por cambios en el protocolo de medición o en el equipo (30,98,181,182) .…”
Section: Estudio Calorimétrico Y Análisis Del Gasto Registrado En La unclassified
“…Algunos estudios han sugerido que la prolongación del tiempo de determinación podría mejorar la precisión y exactitud del GER medido cuando no existe un entrenamiento previo del sujeto, puesto que se ha visto una tendencia a la hiperventilación durante los primeros minutos del registro. Sin embargo, también se ha observado que con determinaciones demasiado prolongadas se pueden obtener lecturas erróneas debidas al agotamiento del sujeto (30,181,182,188) . Estos efectos se documentaron fundamentalmente con el uso de mascarillas.…”
Section: Estudio Calorimétrico Y Análisis Del Gasto Registrado En La unclassified
See 2 more Smart Citations